Cortical Plasticity and Olfactory Function in Early Blindness - Araneda, Rodrigo; Renier, Laurent A.; Rombaux, Philippe; Cuevas, Isabel; De Volder, Anne G. (Frontiers in Systems Neuroscience, 2016)
Over the last decade, functional brain imaging has provided insight in the maturation processes and has helped elucidate the pathophysiological mechanisms involved in brain plasticity in the absence of vision. In case of congenital blindness, drastic changes occur within the deafferented “visual” cortex that starts receiving and processing nonvisual inputs, including olfactory stimuli. This functional reorganization of the occipital cortex gives rise to compensatory perceptual and cognitive mechanisms that help blind persons to achieve perceptual tasks, leading to superior olfactory abilities in these subjects. This view receives support from psychophysical testing, volumetric measurements and functional brain imaging studies in humans, which are presented here.